Elevated psychopathy scores among mixed sexual offenders: replication and extension - Brown, Allison R. (Criminal justice and behavior, 2015)
Past research has revealed a relationship between sexual offending and psychopathy. Notably, offenders who sexually assault a minor as well as an adult (mixed offenders) score higher on the Psychopathy Checklist-Revised (PCL-R) than child sex offenders, rapists, and nonsex offenders. Moreover, both PCL-R Factor 1 (interpersonal-affective traits) and PCL-R Factor 2 (impulsive-antisocial traits) scores have been implicated in explaining these higher psychopathy scores. Using data from 2,514 male prisoners, focusing on a subset of 40 mixed offenders, we attempted to replicate and clarify these findings. As predicted, mixed offenders scored higher on PCL-R total and Factor 1 than other offender groups. Given this distinctive profile, greater understanding of the association between these psychopathic traits and mixed sexual offending may be crucial for evaluating and treating sex offenders as well as for reducing victimization.